The Effect of Cerium Oxide (CeO2) on Ischemia-Reperfusion Injury in Skeletal Muscle in Mice with Streptozocin-Induced Diabetes - Abdullah Özer; Necmiye Şengel; Ayşegül Küçük; Zeynep Yığman; Çağrı Özdemir; Yiğit Kılıç; Ali Doğan Dursun; Hasan Bostancı; Gülay Kip; Mustafa Arslan (Medicina, 2024)
Objective: Lower extremity ischemia-reperfusion injury (IRI) may occur with trauma-related vascular injury and various vascular diseases, during the use of a tourniquet, in temporary clamping of the aorta in aortic surgery, or following acute or bilateral acute femoral artery occlusion. Mitochondrial dysfunction and increased basal oxidative stress in diabetes may cause an increase in the effects of increased reactive oxygen species (ROS) and mitochondrial dysfunction due to IRI. It is of great importance to examine therapeutic approaches that can minimize the effects of IRI, especially for patient groups under chronic oxidative stress such as DM. Cerium oxide (CeO2) nanoparticles mimic antioxidant enzymes and act as a catalyst that scavenges ROS. In this study, it was aimed to investigate whether CeO2 has protective effects on skeletal muscles in lower extremity IRI in mice with streptozocin-induced diabetes. Methods: A total of 38 Swiss albino mice were divided into six groups as follows: control group (group C, n = 6), diabetes group (group D, n = 8), diabetes–CeO2 (group DCO, n = 8), diabetes–ischemia/reperfusion (group DIR, n = 8), and diabetes–ischemia/reperfusion–CeO2 (group DIRCO, n = 8). The DCO and DIRCO groups were given doses of CeO2 of 0.5 mg/kg intraperitoneally 30 min before the IR procedure. A 120 min ischemia–120 min reperfusion period with 100% O2 was performed. At the end of the reperfusion period, muscle tissues were removed for histopathological and biochemical examinations. Results: Total antioxidant status (TAS) levels were found to be significantly lower in group DIR compared with group D (p = 0.047 and p = 0.022, respectively). In group DIRCO, total oxidant status (TOS) levels were found to be significantly higher than in group DIR (p < 0.001). The oxidative stress index (OSI) was found to be significantly lower in group DIR compared with group DCO (p < 0.001). Paraoxanase (PON) enzyme activity was found to be significantly increased in group DIR compared with group DCO (p < 0.001). The disorganization and degeneration score for muscle cells, inflammatory cell infiltration score, and total injury score in group DIRCO were found to be significantly lower than in group DIR (p = 0.002, p = 0.034, and p = 0.001, respectively). Conclusions: Our results confirm that CeO2, with its antioxidative properties, reduces skeletal muscle damage in lower extremity IRI in diabetic mice.